Jihad Joe : Americans Who Go to War in the Name of Islam - Berger, J. M. (John M.), 1967- (Book collections on Project MUSE., 2011)
Describes incidents of Americans volunteering to fight in the name of Islam, including Americans who participated in the 1979 siege of Mecca and conflicts in Lebanon, Afghanistan, Bosnia, and Somalia, and profiling Abdullah Rashid, Mohammed Loay Bayazid, Ismail Royer, Adam Gadahn, and Anwar Awlaki.